Profitability Function on Capital Adequacy Ratio Model - Yudhia Mulya; Dameria BR Girsang; Yuli Zain (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to look at the relationship between the variables NIM, Loan to Deposit Ratio (LDR), Current Exchange Rate (CER), and Capital Adequacy Ratio (CER). This is predicated on the observation that multiple prior studies have yielded differing results, which motivates academics to conduct additional study. This study used 10 cross-sectional samples and a six-year time series with panel data multiple regression analysis. It is classified as quantitative descriptive research. This research formula uses NIM as an intervening variable with the goal of maximizing the CAR value. The primary focus of this research is the banking businesses that are listed on the Indonesian Stock Exchange. The use of multiple regression analysis is made to investigate panel data techniques, and two integrated research models are created into a single study model. The first study model's findings support the relevant theory by showing that CER can positively correlate its effect on NIM. Another finding in the second research model is that NIM has a positive association with its influence on CAR, which is consistent with the relevant theory. Only the relationship between CER and CAR can be explained by the NIM function as an intervening variable. It is envisaged that these findings would serve as a manual for Indonesian banking professionals to help them optimize the capital adequacy ratio